The role of sickness in the evaluation of job search assistance and sanctions - Gerard J. van den Berg; Barbara Hofmann; Arne Uhlendorff (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
Unemployment insurance agencies may combat moral hazard by punishing refusals to apply to assigned vacancies. However, the possibility to report sick creates an additional moral hazard, since during sickness spells, minimum requirements on search behavior do not apply. This reduces the ex ante threat of sanctions. We analyze the effects of vacancy referrals and sanctions on the unemployment duration and the quality of job matches, in conjunction with the possibility to report sick. We estimate multi-spell duration models with selection on unobserved characteristics. We find that a vacancy referral increases the transition rate into work and that such accepted jobs go along with lower wages. We also find a positive effect of a vacancy referral on the probability of reporting sick. This effect is smaller at high durations, which suggests that the relative attractiveness of vacancy referrals increases over the time spent in unemployment. Overall, around 9% of sickness absence during unemployment is induced by vacancy referrals. – – Ein Instrument zur Eindämmung von Moral Hazard in der Arbeitslosenversicherung ist die finanzielle Sanktion in Form einer Sperrzeit. Da jedoch während Krankheitsperioden keine Mindestanforderungen an Suchanstrengungen von Arbeitslosen gelten, entsteht durch die Möglichkeit, sich krank zu melden ein zusätzlicher Moral Hazard. Dies wiederum verringert die Drohwirkung von Sperrzeiten. Unter Berücksichtigung der Möglichkeit, sich krank zu melden, analysieren wir die Auswirkungen von Vermittlungsvorschlägen und Sperrzeiten auf die Dauer der Arbeitslosigkeit und die Qualität der aufgenommenen Jobs.Wir schätzen Multi-Spell Verweildauermodelle mit Selektion basierend auf unbeobachteten Merkmalen. Wir zeigen, dass ein Vermittlungsvorschlag die Übergangsrate in Beschäftigung erhöht und dass dies mit geringeren Löhnen einhergeht.Wir finden auch positive Effekte eines Vermittlungsvorschlags auf die Wahrscheinlichkeit einer Krankmeldung. Dieser Effekt ist geringer in späteren Monaten der Arbeitslosigkeit. Dies legt nahe, dass die relative Attraktivität der Vermittlungsvorschläge im Verlauf der Arbeitslosigkeit ansteigt. Unseren Ergebnissen zufolge sind insgesamt etwa 9 Prozent der Krankmeldungen während der Arbeitslosigkeit ausgelöst durch Vermittlungsvorschläge.
Keywords: J64; J65; C41; C21; 330; unemployment; vacancy referrals; physician; wage; unemployment insurance; monitoring; moral hazard; Arbeitslosenversicherung; Moral Hazard; Arbeitslosigkeit; Dauer; Offene Stellen; Krankheit; Anreiz; Theorie; Schätzung; Deutschland